PEMANFAATAN SIPLAH UNTUK BELANJA KEBUTUHAN SEKOLAH - Giawa, Yulina; Zagoto, Lidwina Shinta; Ritonga, Roy Ricardo; Manik, Efron; Hutauruk, Agusmanto (Universitas Quality, 2023)
This research aims to find out how effective the procurement of BOS goods in the private SMP of BNKP Luzamanu, find obstacles, and solutions in the provision. The type of research used is a qualitative descriptive type and supported by secondary data. The technique used is a triangulation method that compares information or data in different ways. The subjects used in this study are the Boss Treasury, the School Operator, the Head of the School, and reinforced with documents in the implementation of the acquisition. Based on the results of the analysis, it can be concluded that the use of SIP applications is very effective in the procurement of BOS goods in the private SMP of BNKP Luzamanu. Some obstacles were found in the implementation of this acquisition, problems arose on resources, adaptation, and price comparison. But that does not make it a fatal thing, because it can be overcome with the help of various parties.